Enhanced antitumor activity of cucurbitacin B combined with cerulenin in osteosarcoma - Zhang, Zhe; Shen, Ying; Wu, Jian; Cai, Lin (Bangladesh Journal of Pharmacology, 2015)
In the present study, the effect of cucurbitacin B and cerulenin combination on osteosarcoma was investigated to develop an effective treatment regimen. The IC50 values of cerulenin and cucurbitacin B combination in the proportion of 1:1, 1:2 and 2:1 were 3.5, 7.2 and 8.6 μg/mL, respectively. The combination index (CI) values of <0.95 for inhibition of growth and <0.93 for inhibition of SENP5 expression clearly indicated synergism between the two. The Q-value for combination of 1 μg/mL cerulenin and 1 μg/mL cucurbitacin B was 1.2. AI calculated for tumor tissues treated with a combination of cucurbitacin B and cerulenin (26.2 ± 8.4%) was higher than that of the tissues treated separately with cucurbitacin B (14.5 ± 6.8%) or cerulenin (12.6 ± 7.5%). The AI for untreated tumor tissues was 4.2 ± 1.5%. Thus, the combination of cucurbitacin B and cerulenin can be a promising regimen in the treatment of osteosarcoma.